2014
DOI: 10.1007/s12098-014-1498-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nebulised Budesonide versus Oral Prednisolone in Acute Severe Asthma

Abstract: Nebulised budesonide significantly improves PEFR levels and fitness for discharge at 2 h when compared to oral prednisolone in children between 5 and 12 y with acute severe asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…; NIH 2020[35], 2 RS[60,61] and 6 RCT[62][63][64][65][66][67].Scientific evidences on these topics are very heterogeneous for all PICO elements: 1. Population: age (adults/ children); asthma step (step 2/not specified); severity of asthma attack (mild, moderate, severe); 2.…”
mentioning
confidence: 99%
“…; NIH 2020[35], 2 RS[60,61] and 6 RCT[62][63][64][65][66][67].Scientific evidences on these topics are very heterogeneous for all PICO elements: 1. Population: age (adults/ children); asthma step (step 2/not specified); severity of asthma attack (mild, moderate, severe); 2.…”
mentioning
confidence: 99%
“…Two randomized clinical trials compared the effectiveness of high-dose of ICS vs, SS [ 42 , 43 ], the results showed that ICS and SS have the same efficacy to improve clinical symptoms. However, one study [ 38 ] showed that in the group treated with high doses of budesonide (800 μg/ 20 min) there was an increase in the percentage of children discharged from hospital after 2 h compared to the group treated with prednisolone (2 mg/kg).…”
Section: Resultsmentioning
confidence: 99%
“…There were 7 studies remaining for the analysis; comprised of three meta-analysis and four added studies. [ 12 13 14 15 16 17 18 ] The three meta-analysis included Edmonds et al ., in 2012; Su et al ., in 2014; and Beckhaus et al ., in 2014. [ 12 13 14 ] The other four RCT studies were added and shown in Table 1 .…”
Section: R Esultsmentioning
confidence: 99%
“…In total, there were 19 studies included in the final analysis. [ 8 9 10 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ] These 19 studies had 20 comparisons between ICS and other treatments; Milani 2004 study had two comparisons; ICS versus placebo and ICS versus SC. The 20 comparisons categorized as ICS versus placebo (5 comparisons), ICS versus SC (11 comparisons), and ICS plus SC versus SC (4 comparisons).…”
Section: R Esultsmentioning
confidence: 99%